The influence of social media advertising on consumer purchase intention and buying behaviour amongst youth in Limpopo Province - Moropana, Clearence (My University, 2023)
The title of this dissertation is the influence of social media advertising on consumer purchase intention and buying behaviour amongst youth in Limpopo Province. The quantitative research approach was applied in this study to investigate how social media advertising influences purchase intention and buying behaviour among consumers especially the youth in Mopani (Giyani and Tzaneen) and Capricorn (Polokwane and Ga Mothapo) Districts. Structured questionnaire was distributed to the target audience to get knowledge regarding their experiences and views on the influence of social media advertising during shopping. The sample size was 384 respondents. Data for this study were analysed through SPSS software. Analysis methods such as multiple regression, regression and correlation were used to test the influence of social media advertising on consumer purchase intention and buying behaviour. The study found that advertising brands through social media platforms are capable of influencing, attracting, and providing trusted information about the product quality among consumers. The study also revealed that there is strong correlation between social media advertising and youth purchase intentions. Moreover, social media advertising influences the youth to a point where purchase intention is developed. Out of 384 respondents 371 youth were likely to make a purchase on the same day of using social media advertising. Mostly, those who are influenced by social media advertising spend more on purchases that are less important to them. The result shows that marketers use psychological, personal, and social factors to arouse consumers’ interests. Customers with a positive attitude towards social media advertising are likely to produce beneficial behavioural actions. The finding revealed that consumers experience financial, social, emotional, and psychological effects after purchasing products. The research also finds significant positive relationship between purchase intention and buying behaviour due to the influence of social media advertising. In this respect, brands sellers could benefit from this research by acquiring a better understanding of social media marketing strategies. Based on the research findings, the researcher recommends that marketers of brands employ social media marketing activities to increase customers purchase intention and buying behaviour.
Thesis (M.A. (Media Studies)) -- University of Limpopo, 2023
Keywords: Social media avertising; Buying behaviour; Consumer purchase; Socialmedia; Advertising; Youth -- South Africa -- Limpopo; Young consumers -- South Africa -- Limpopo